Reducing Labor Pain through Endorphin Massage: Clinical Evidence from Indonesia - Sartika, Sartika; Noorlinda, Noorlinda (Journal of Current Health Sciences, 2025)
Labor pain remains a critical challenge in maternal care, especially in resource-limited settings where access to pharmacological analgesia is restricted. Endorphin massage, a non-pharmacological intervention, offers a safe and evidence-based alternative, yet robust clinical data remain limited. This quasi-experimental study, conducted at Pancatengah Public Health Center, Indonesia, involved 15 mothers in active labor who received standardized endorphin massage during the first stage of labor. Pain intensity was measured pre- and post-intervention using a Numeric Rating Scale. Statistical analysis with the Mann-Whitney U test revealed a significant reduction in pain scores (p = 0.011; effect size r = 0.65), with most participants shifting from moderate or severe pain to mild or no pain, and no adverse events observed. These findings highlight the clinical and practical value of endorphin massage as a safe, accessible pain management strategy. Further studies with larger, controlled samples are recommended to confirm generalizability and address implementation challenges. Abstrak: Nyeri persalinan masih menjadi tantangan utama dalam pelayanan maternal, khususnya di wilayah dengan keterbatasan akses analgesia farmakologis. Pijat endorfin sebagai intervensi non-farmakologis menawarkan alternatif yang aman dan berbasis bukti, meskipun data klinis yang kuat masih terbatas. Penelitian kuasi-eksperimen ini dilakukan di Puskesmas Pancatengah, Indonesia, melibatkan 15 ibu bersalin pada kala I aktif yang menerima pijat endorfin terstandar. Intensitas nyeri diukur sebelum dan sesudah intervensi menggunakan Numeric Rating Scale. Analisis statistik dengan uji Mann-Whitney menunjukkan penurunan skor nyeri yang signifikan (p = 0,011; effect size r = 0,65), dengan mayoritas responden mengalami perubahan dari nyeri sedang/berat menjadi ringan atau tanpa nyeri, dan tidak ditemukan efek samping. Temuan ini menegaskan nilai klinis dan praktis pijat endorfin sebagai strategi manajemen nyeri yang aman dan mudah diakses. Studi lanjutan dengan desain terkontrol dan sampel lebih besar direkomendasikan untuk mengonfirmasi generalisasi serta mengatasi tantangan implementasi.